The Influence Of Country, Firm And Individual Factors On Knowledge Transfer Efficiency Among Chinese Multinational Corporations - Cheng, Junshuai (2022)
With the advent of the era of knowledge and information, knowledge management has become a concern of global corporations. Moreover, multinational Corporations (MNCs) played an increasingly important role in the development of the global economy. Knowledge transfer in MNCs has been one of the key challenges in the competitive era. However, from the summary and analysis of research on knowledge transfer in previous research, it easily found that the research issues were more one-sided and not profound. Especially, for China, with special culture and environment, the current research could not solve the practical problems. The main objectives of this study were to establish a completed framework and test the influencing factors of knowledge transfer efficiency in Chinese MNCs. Therefore, this study focused on the field of knowledge transfer in MNCs and used a holistic perspective to study the influencing factors on knowledge transfer efficiency. The proposed research framework of this study is supported by knowledge transfer and social network theory, combined with previous research results synthesized, and suggests a new model. This study considers country level factors (regulative distance, normative distance and cognitive distance), firm level factors (subsidiary autonomy, subsidiary position and organizational trust) and individual level factors (cultural intelligence and work performance) as independent variables, and subsidiary characteristics (subsidiary age and subsidiary size) as moderating variable, predicting its impact on the factors towards efficiency of knowledge transfer as the dependent variable. This research adopts the questionnaire survey method for data collection from the target respondents of expatriates working in Chinese MNCs. Data collected will be analyzed with SPSS and smart-PLS in order to test the hypotheses developed. From the theoretical perspective, based on the results of data analysis of 212 subsidiaries of Chinese multinational corporations, this study contributed to the knowledge transfer theory and efficiency by addressing gaps identified from existing research